RESPONS MAHASISWA DALAM MEMANDANG KARYA DOSEN IAIN PURWOKERTO - Abdul Wachid B.S; Dewandaru Ibrahim Senjahaji (IAIN Purwokerto, 2017)
Abstract: This paper aims to find out the response of students in looking at the works of lecturers at IAIN Purwokerto and to know the absorption of students to the knowledge delivered by lecturers who have works (modules or textbooks). The results of this study found that Purwokerto's IAIN students had quite interesting views on the lecturers' works displayed in lectures to inspire. They also want to work by generating ideas, only lacking direction. Students' absorption of knowledge delivered by lecturers who have works (modules or textbooks) is realized through three things, namely through efforts to make their works published in the form of books (joint and single anthologies), publishing works in mass media (newspapers, journals, or magazine), and participation in competitions featuring works. The direction and guidance from the lecturers make them produce creative and innovative power in a race that has strict supervision. In this published domain, the seriousness of the work of students can be tested, besides they will later produce works in the form of a thesis as research at the end of the learning process. Keywords: Response, Work, Lecturer, Student, Learning